The impact of COVID-19 on medical education: our students perception on the practice of long distance learning - Daroedono, Ekarini; Siagian, Forman E.; Alfarabi, Muhammad; Cing, Jap Mai; Arodes, Evy S.; Sirait, Robert H.; Suryowati, Trini; Sunarti, Lusia S.; Ahmad, Luana N.; Wiyanto, Marwito; Kurniaty, Linggom; Hutabarat, Roni S. O. (International Journal Of Community Medicine And Public Health, 2020)
Background: Medical faculties in Indonesia also affected by COVID-19 pandemic, including the faculty of medicine, Universitas Kristen Indonesia. To some extent, faculty administrator had to improvisize in order to make adjustment, from the formerly class based lecture in to modified long distance/online lecture. This study aimed to measure the impact of COVID-19 on the medical education by asking the student’s perception on the practice of long distance learning delivered during this pandemi. Methods: The study held in Jakarta, Indonesia from the 1st until 3rd week of May 2020, after previously being approved by the faculty ethical committe. This is a simple survey based cross sectional study design using electronic questionairre which was arranged based on the result of previously conducted small focus group discussion and in-depth interview carried out on a number of selected students and lecturers. Questionairre made on Google Forms™, then carefully being evaluated for its validity and reliability until considered fix. The e-questionairre sent via whatsapp™ to all of students. All the data collected put together in Microsoft Excel spreadsheet, then being exported to SPSS™ ver. 21 for further analysis. Results: A number of 545 students respondended to electronic survey conducted via WhatsApp™. Our study on the effect of COVID to our student’s education revealed some supportive, but also inhibitory factors. Conclusions: To our knowledge, this can be a valuable input to faculty administrator in order to improve medical education delivery in the future.